Osteoma of Mastoid Bone; A Rare Presentation: Case Report - Kandakure, Vinod T. (Indian J Otolaryngol Head Neck Surg, 2016)
Mastoid osteomas are benign, slow growing tumours arising in temporal bone. These are rare; few cases reported till date. Normally are asymptomatic, may present with cosmetic deformity, pain and hearing loss. These are readily excised. Recurrence is rare.